A Desk Review of The Application of Data Analytic on Tesla Inc. - Firmansyah, Mulya (International Journal of Information Technology and Computer Science Applications, 2025)
Tesla Inc. is frequently regarded as a pioneer in the fields of big data analytics and artificial intelligence. They generate, collect, and analyse a large amount of data every day for a better decision-making for their business and for their self-driving car. However, a little effort was put into marketing. Customer segmentation and customer retention are noticed to be the problems Tesla Inc. should take into consideration. Therefore, the data that is relevant to solve these problems is extracted from various websites and social media platforms by using the text-scrapping technique. Web analytics of Tesla’s official website is studied to analyse the demographic and geographic details of the audiences. Geospatial analysis is also carried out to further analyse the top 5 countries the audiences are coming from. Customers' reviews that were collected undergoes sentiment analysis to determine whether it is positive, neutral, or negative. Text analytics is done in the later stage by gathering all the visualisations into an interactive dashboard and coming up with a possible solution.